Identifikasi Penggunaan Sumber Air Bersih dan Jamban Rumah Tangga Terhadap Riwayat Sakit pada Anak Usia 6-59 Bulan di Pesisir Pantai Kabupaten Karawang - Linda Riski Sefrina; Ratih Kurniasari; Milliyantri Elvandari; Annisa Ratri Utami; Asep Malinda Aiboga (Program Studi Gizi UNSIKA, 2022)
Previous studies have shown that illness, especially infectious diseases, is a risk factor for malnutrition in children aged 6-59 months. Environmental sanitation is an important factor that influences the occurrence of infection. The purpose of this study was to assess the relationship between the use of clean water sources and the use of household latrines with a history of diseases in children aged 6-59 months. This study used a cross-sectional design with 108 research subjects. Research subjects were selected using accidental sampling. Collecting data using interview and observation techniques. The results showed that there was no significant relationship between the type of source of drinking water, type of source of washing water, type of latrines, and ownership of latrines with a history of diseases in the research subjects. The history of diseases in the research subjects was significantly related to the distance between the water source and the waste disposal site (p-value <0.05). Based on these results, further efforts are needed to improve environmental sanitation in coastal areas to prevent an increase in morbidity in children under five.